Potret Perempuan dalam Novel Manusia Bebas Karya Suwarsih Djojopuspito - Ridwan, Ridwan; Ramadhani, Fitri (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
This research aims to express the portrait of women in the novel Manusia Bebas by analyzing the feminist literary criticism approach that provides another space in literary appreciation and criticism. The analysis conducted by examining the novel Manusia Bebas by Suwarsih Djojopoespito uses the repeated reading method and the qualitative descriptive method so that it is possible to open up space for interpretation regarding female characters and their position in the novel. The qualitative research method is also known as the interpretative method because the research data is more related to the interpretation of the data found in the field. The results of the research on the novel